An SFL Analysis of Interpersonal Metafunction in Constructing President Prabowo's Moral Authority at the UNGA - Rafiq al indra; Nur Aisyah Zulkifli (Universitas Islam Negeri Palopo, 2026)
This study presents an SFL (Systemic Functional Linguistics) analysis of the Interpersonal Metafunction in President Prabowo's UNGA speech, focusing on the Mood and Modality systems to uncover the rhetorical strategies used in constructing his moral authority and negotiating Indonesia's role as a committed global actor. The analysis finds that while the Declarative Mood dominates to establish credibility, strategic shifts to the Interrogative Mood and the inclusive Imperative Mood (